PENGARUH ENVIRONMENTAL MANAGEMENT SYSTEM TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI - Mick Jovi Brucelee Manueke; Francis Hutabarat; Judith Tagal Gallena Sinaga (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2026)
Abstract: This research aims to analyze the influence of implementing the ISO 14001 Environmental Management System on Firm Value, with Corporate Governance as a moderating variable. Stakeholder theory is used as a theoretical foundation and emphasizes the importance for companies to consider the interests of stakeholders thru sustainability initiatives and corporate governance. The research method used is quantitative, with secondary data obtained from annual reports and sustainability reports. The research sample consists of fifteen banks included in the JKBank15 Index during the period from 2018 to 2024. Data analysis was conducted using descriptive statistics, regression with a moderating variable, and simple slope testing with the assistance of Jamovi software. The research results indicate that the Environmental Management System ISO 14001 has a positive and significant effect on Firm Value. Additionally, Corporate Governance also has a significant effect on PBV and is able to strengthen the influence of the Environmental Management System ISO 14001 on Firm Value. This finding suggests that Corporate Governance has a moderating effect that enhances the relationship between the Environmental Management System ISO 14001 and Firm Value. Therefore, high Corporate Governance standards and practices can strengthen the impact of implementing the Environmental Management System ISO 14001 on increasing Firm Value, while when the role of Corporate Governance is low, the influence of the Environmental Management System on Firm Value becomes insignificant.